2014
DOI: 10.1002/sia.5411
|View full text |Cite
|
Sign up to set email alerts
|

Energy dependence of the energy loss function parametrization of indium in the Drude–Lindhard model

Abstract: The energy loss function (ELF) is a key parameter for the calculations of energy losses undergone by electrons in matter. It is often the only input in the calculations performed within the models based on the semi-classical dielectric response theory. Its perfect knowledge is thus of primordial importance. To evaluate the ELF, it is usual to consider as a model an expansion in Drude-Lindhard (DL) type oscillators with fixed values of the strength, width, energy and dispersion for the various oscillators. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The Al/In interface has been chosen for its academic interest rather than its practical importance. Indeed each of the two materials exhibits only one plasmon peak in its ELF 13,16 . Figure 1 shows the local‐DIIMFP μ12false(E,α,ω,rfalse) for a 500‐eV electron travelling from Al to In and from In to Al at various distances from the interface crossing point (with the interface crossing angle α=0°).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Al/In interface has been chosen for its academic interest rather than its practical importance. Indeed each of the two materials exhibits only one plasmon peak in its ELF 13,16 . Figure 1 shows the local‐DIIMFP μ12false(E,α,ω,rfalse) for a 500‐eV electron travelling from Al to In and from In to Al at various distances from the interface crossing point (with the interface crossing angle α=0°).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed each of the two materials exhibits only one plasmon peak in its ELF. 13,16 Figure 1 shows the local-DIIMFP μ 1!2 ðE, α, ℏω, rÞ for a 500-eV electron travelling from Al to In and from…”
Section: Local-diimfpmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the width of this loss function did depend on the incoming electron energy, whereas the dielectric function of a material should describe REELS measurements taken at any energy. Pauly suggested that this could be explained by assuming that Γ depends on q , as the ranges of q values contributing to the spectrum (see the integration limits in Eqn ) changes with incoming electron energy . Calliari et al .…”
Section: Resultsmentioning
confidence: 99%